Impact of chronic total occlusion in non-culprit vessels on long-term survival of patients with acute myocardial infarction. (25th November 2020) - Nakazato, K; Ando, T; Kiko, T; Shimizu, T; Oikawa, M; Yamaki, T; Kunii, H; Yoshihisa, A; Takeishi, Y
Abstract: Background: Around 10% of patients with acute myocardial infarction (AMI) have chronic total occlusion (CTO) in non-infarct-related vessels, and they are known to be associated with higher mortality in acute phase. However, its impact on long-term prognosis after discharge remains unclear. Purpose: The purpose of this study was to investigate the influence of presenting CTO lesion on long-term prognosis in patients with AMI. Method: Consecutive 552 patients with AMI (male 78.3%, age 68±13 years), who had been discharged alive from our hospital, were analyzed. We divided the patients into two groups based on whether they had CTO lesion in a non-infarct-related artery or not: CTO + (n=49) and CTO - (n=503). Results: Kaplan-Meier analysis (mean follow-up 1, 424 days) revealed that all-cause mortality was significantly higher in CTO + group than in CTO - group (Figure, P<0.001). Cox hazard ratio was 2.740, indicating a higher risk of all-cause death in the CTO + group (95% CI 1.606–4.651, P<0.001). Conclusion: Concurrent coronary CTO lesions in non-culprit arteries were associated with increased long-term mortality in patients with AMI. Funding Acknowledgement: Type of funding source: None